2012
DOI: 10.1099/ijs.0.038265-0
|View full text |Cite
|
Sign up to set email alerts
|

Mesorhizobium muleiense sp. nov., nodulating with Cicer arietinum L.

Abstract: Three chickpea rhizobial strains (CCBAU 83963 T , CCBAU 83939 and CCBAU 83908), which were identified previously as representing a distinctive genospecies, were further studied here and compared taxonomically with related species in the genus Mesorhizobium. Results from SDS-PAGE of whole-cell soluble proteins revealed differences from closely related recognized species of the genus Mesorhizobium. ; only Cicer arietinum, its host plant, could be invaded to form effective nitrogen-fixing nodules. The narrow sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 26 publications
(28 reference statements)
1
27
0
2
Order By: Relevance
“…Our results are in accordance with previous studies based on a large number of isolates showing that nifH phylogenies are broadly similar to those of nodulation genes [30]. In the particular case of Mesorhizobium spp.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in accordance with previous studies based on a large number of isolates showing that nifH phylogenies are broadly similar to those of nodulation genes [30]. In the particular case of Mesorhizobium spp.…”
Section: Discussionsupporting
confidence: 94%
“…Cohen et al (2009) in a similar study suggested that ABA produced along with gibberellins by PGPR strain significantly contributed to water stress alleviation of maize plants. Some rhizobial strains such as B. japonicum USDA110 also produce ABA (Boiero et al 2007) and function in the same way as do the other PGPR (Zhang et al 2012). …”
Section: Negative Plant Growth Regulatormentioning
confidence: 96%
“…Several other chickpea rhizobia belonging to known species in the genus Mesorhizobium have also been detected in Spain and Portugal [13]. Despite the diversity of Mesorhizobium species nodulating chickpea, the highly conserved symbiotic genes nodC and nifH are shared across these species [9,13,23,24]. Most recently, Armas-Capote et al reported that more than nine Mesorhizobium genospecies could nodulate Cicer canariense in a natural habitat on La Palma, Canary Islands [2].…”
Section: Introductionmentioning
confidence: 94%
“…Chickpea nodulation and rhizobial inoculation have been studied intensively in many countries during the last three decades [2,[14][15][16]. Three main rhizobial species specifically nodulating chickpea have been described: Mesorhizobium ciceri and Mesorhizobium mediterraneum in Spain [1,11,12], and Mesorhizobium muleiense in Xinjiang, China [23]. Several other chickpea rhizobia belonging to known species in the genus Mesorhizobium have also been detected in Spain and Portugal [13].…”
Section: Introductionmentioning
confidence: 99%